Comprehensive landscape of cell death mechanisms: from molecular cross-talk to therapeutic innovation in oncology - Qi, Ke; Mu, Yongping; Hu, Yang; Li, Jiayi; Liu, Jia (Frontiers in Cell and Developmental Biology, 2025)
Cell death, or programmed cellular termination, represents a fundamental biological phenomenon crucial for maintaining organismal homeostasis. Traditionally conceptualized as a passive terminal state associated with inflammatory responses and elimination of compromised cells, contemporary research has unveiled cell death as a sophisticated regulatory network encompassing diverse modalities, including apoptosis, necrosis, autophagic cell death, and lysosomal cell death, which are classified as programmed cell death, and pyroptosis, necroptosis, and NETosis, which are classified as inflammatory cell death, have been described over the years. Recently, several novel forms of cell death, namely, mitoptosis, paraptosis, immunogenic cell death, entosis, methuosis, parthanatos, ferroptosis, autosis, alkaliptosis, oxeiptosis, cuproptosis, erebosis and disulfidptosis, have been discovered and advanced our understanding of cell death and its complexity. This synthesis examines the historical progression and defining characteristics of cellular termination pathways, with particular emphasis on their molecular regulation and pathophysiological significance. The mechanistic diversity of these processes not only reveals intricate cellular quality control systems but also provides therapeutic opportunities for neoplastic diseases. For instance, investigations into oncogenic regulators like B-cell lymphoma 2 (BCL-2) family proteins have illuminated the critical relationship between apoptotic resistance and malignant progression, catalyzing development of pro-apoptotic agents such as BH3 mimetics. Strategic integration of these targeted therapies with conventional cytotoxic regimens and immunomodulatory approaches represents a promising frontier in precision oncology, potentially enhancing therapeutic efficacy while mitigating adverse effects in cancer management.